A gesture-based design tool: Assessing 2DOF vs. 4DOF steerable instrument control. - E A Arkenbout; J C F de Winter; A Ali; J Dankelman; P Breedveld (PLoS ONE)
Iterative prototyping is costly and time-consuming. Particularly when designing medical instruments, human factors related design choices significantly impact performance and safety. A tool is presented that allows for the evaluation of steerable instrument controls before the onset of the prototyping stage. The design tool couples gestural input to virtually simulated instrument motions using hand motion tracking. We performed a human-subject evaluation of two manual control strategies that differed in their degrees of freedom (DOF). 2DOF thumb control was compared to 4DOF thumb-index finger control. Results identified regions within the instrument workspace that are difficult to reach and showed participants to favor using the thumb for gross and fine-tuning motions at both control strategies. Index finger ab/adduction was found to be least functional. A strong learning effect was observed at 4DOF control. Based on the results, gesture-based instrument design is a viable design tool.